Development of high-performance ScS2 monolayer as cathode material: A DFT analysis. (1st September 2022) - Al Roman, Abdullah; Rahman, M Mahbubur; Hossain, Kamal; Das, Sudipto; Ahmed, Farid
Abstract: Electrode host materials primarily determine the electronic and electrochemical properties such as adsorption, electrical and ionic conductivity, charge storage capacity, discharge voltage and maintain the structural stability of ion-storage devices. Here we employed a first-principles approach to investigate the possibility of these properties in ScS2 monolayer as a transition metal dichalcogenide (TMD). It is found that the ScS2 monolayer could be engaged as a potential cathode host material in rechargeable Li, Na and Ca ion-storage batteries with maximum specific capacities of 491.38 mAh/g, 491.38 mAh/g and 982.76 mAh/g respectively. Employing this material as an intercalation host a 3.61 V, 2.68 V and 1.93 V, respectively, averaged electrode potential could be achieved for Li, Na and Ca. The ScS2 monolayer shows good electronic conductivity throughout the intercalation process and offers fast diffusion kinetics for alkali metal ions (Li + and Na + ) with barrier height not more than 0.34 eV but comparatively sluggish diffusion kinetics for Ca 2+ . The ScS2 monolayer may be used in ion-storage batteries with fast/moderate diffusion mobility to achieve equivalent voltage but significantly higher specific capacity. Highlights: A first-principles approach is used to realize the 1 TT-ScS2 monolayer as the cathode host material for metal-ion batteries. A very high specific capacity was offered by the 1 TT-ScS2 monolayer as the cathode host material. A maximum open-circuit voltage of 3.61 V was found for the Li-ion storage batteries. The 1 TT-ScS2 monolayer offers fast diffusion kinetics for alkali metal ions.